Methodological challenges and advances in managerial and organizational cognition - Galavan, Robert; Sund, Kristian J., 1975-; Hodgkinson, Gerard P., 1961- (New horizons in managerial and organizational cognition, 2017)
This book explores the methodological frontiers of managerial and organizational cognition (MOC), an exciting and divisive interdisciplinary body of work that began with the publication in 1958 of James G. March and Herbert A. Simon's classic work Organizations. Entering its fourth decade, the field gained significant momentum following the appearance of Anne S. Huff's (1990) book Mapping Strategic Thought, which explored the (then) methodological frontiers of MOC. The world has changed since then and so, too, have the methods available to MOC researchers; it is timely, therefore, to examine the extent to which the methods that were foundational to the development of MOC are still fit for purpose. Taking stock of MOC's many methodological accomplishments, the thought-provoking chapters comprising this second volume of the New Horizons in Managerial and Organizational Cognition book series set the agenda for the next phase of the field's development.